Contribution of Antarctica to past and future sea-level rise - DeConto, Robert M.; Pollard, David (Nature (London), 2016)
Polar temperatures over the last several million years have, at times, been slightly warmer than today, yet global mean sea level has been 6–9 metres higher as recently as the Last Interglacial (130,000 to 115,000 years ago) and possibly higher during the Pliocene epoch (about three million years ago). In both cases the Antarctic ice sheet has been implicated as the primary contributor, hinting at its future vulnerability. Here we use a model coupling ice sheet and climate dynamics—including previously underappreciated processes linking atmospheric warming with hydrofracturing of buttressing ice shelves and structural collapse of marine-terminating ice cliffs—that is calibrated against Pliocene and Last Interglacial sea-level estimates and applied to future greenhouse gas emission scenarios. Antarctica has the potential to contribute more than a metre of sea-level rise by 2100 and more than 15 metres by 2500, if emissions continue unabated. In this case atmospheric warming will soon become the dominant driver of ice loss, but prolonged ocean warming will delay its recovery for thousands of years. Climate and ice-sheet modelling that includes ice fracture dynamics reveals that Antarctica could contribute more than a metre of sea-level rise by 2100 and more than 13 metres by 2500, if greenhouse gas emissions continue unabated. A 500-year model of Antarctica's contribution to future sea-level rise Robert DeConto and David Pollard use a newly improved numerical ice-sheet model calibrated to Pliocene and Last Interglacial sea-level estimates to develop projections of Antarctica's evolution over the next five centuries, driven by a range of greenhouse gas scenarios. The modelling shows that the Antarctic ice sheet has the potential to contribute between almost nothing, to contributing more than a metre of sea-level rise by 2100 and more than 15 metres by 2500. The startling high-end estimate arises from unabated emissions and previously underappreciated mechanisms: ice-fracturing by surface meltwater and collapse of large ice cliffs. The low end shows that a scenario of strong climate mitigation can radically reduce societal exposure to higher sea levels.